PKM Pendampingan Kinerja Kepemimpinan OSIM melalui Inovasi Manajemen Pembelajaran di MTsN 1 Probolinggo - Yaqin, Muhammad Ainul; Huda, Miftahul; Sholahuddin, Sholahuddin (Lembaga Pengembangan Kinerja Dosen, 2025)
The low effectiveness of student organizational performance in designing and managing structured work programs presents a major challenge to strengthening the leadership culture at MTsN 1 Probolinggo. This community service program aims to enhance students’ managerial and leadership capacities through performance mentoring for the Intra-Madrasah Student Organization (OSIM), based on innovations in learning management. The methods employed include training sessions, workshops, and continuous mentoring, all designed collaboratively with school stakeholders. The activity stages began with a needs analysis and problem mapping, followed by the development of training modules, the implementation of organizational management training, and interactive workshops aimed at developing adaptive and applicable work programs. The proposed solutions encompass strengthening foundational understanding of organizational management, enhancing the role of members in program planning, and facilitating the implementation of OSIM activities that support the creation of an active learning environment. Evaluation was carried out through pre-tests and post-tests to measure comprehension improvement, field activity observations, and assessments of work program achievement. The results indicate significant improvements in participants’ cognitive and practical skills, particularly in the planning, execution, and evaluation of OSIM programs that are now more structured and goal-oriented. In conclusion, this community service activity successfully reinforced student leadership competencies through an innovative approach to managing student organizations, while also promoting the development of a sustainable culture of collaborative work. Based on the outcomes, it is recommended that this mentoring model be replicated in other madrasahs and that OSIM leadership development programs be systematically integrated into extracurricular curricula to ensure the continuity and expansion of the positive impacts achieved